Spatially varying relationships between risk factors and child diarrhea in West Africa, 2008-2013. Issue 1 (2nd January 2020) - Dunn, Gillian; Johnson, Glen D.; Balk, Deborah L.; Sembajwe, Grace
ABSTRACT: Diarrhea is a major contributor to child morbidity and mortality in West Africa. Non-spatial regression and geographically weighted Poisson regression applied to data from 10 Demographic and Health Surveys conducted in West Africa from 2008 to 2013 show that water source, toilet type, mother's education, latitude, temperature, rainfall, altitude, and population density influence the risk of diarrhea. The risk associated with these factors is dependent on location and may be higher or lower than the rest of the study area. Areas with increased relative risk for diarrhea include several urban centers, low-elevation areas (coastal and along rivers), remote areas such as western Mali, and conflict zones (northeast Nigeria).